Integration of Differentiated Learning and Counseling: Development of an ADDIE-Based Module to Reduce Student Boredom - Albab, Bintang Ulul; Isriyah, Mudafiatun; Ulwiyah, Imaratul (Konseling Edukasi : Journal of Guidance and Counseling, 2026)
Integration of Differentiated Learning and Counseling: Development of an ADDIE-Based Module to Reduce Student Boredom. This study aims to develop a module based on a differentiation and counseling approach as an effort to reduce learning boredom among students at the Ibnu Katsir 1 Islamic Boarding School in Jember. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The limitations of this study focused on the development and limited trials involving four students at the research site. The assessment results showed that the module was very feasible to use with a validation score of 83% from material experts, 82% from language experts, and 81% from practitioners' assessments. The results of the field trial showed a significant decrease in the level of learning boredom among the research subjects. The implications of this study provide practical contributions for Islamic boarding school managers in implementing more personalized and adaptive learning strategies. The use of this module allows educators to address psychological barriers among students in a structured manner through the integration of counseling techniques into the curriculum. Thus, this module can be a reference for mental health and academic intervention models in boarding-based educational environments.Keywords: Differentiated Approach; Counseling; Learning Saturation